Clinical Profile of Turner Syndrome: A Tertiary Center Experience - Dhanya Soodhana Mohan; Avani Hegde; Vani Hebbal Nagarajappa; Raghupathy Palany (Dubai Diabetes and Endocrinology Journal)
Background: Turner syndrome (TS) is the commonest chromosomal abnormality in females with an incidence of 25–50 per 100,000 females. Girls with TS universally have short stature (95%), along with gonadal failure (>90%) and infertility (99%); however, the ethnic differences are not well elaborated. Objectives: This study has been planned to evaluate the presentation and course of Indian girls with TS. Methods: Patients with TS presenting to our referral endocrinology clinic were included in this study. Diagnosis of TS was done by karyotyping. A retrospective chart review of these patients formed the basis of this study. Results: A total of 55 patients with TS karyotype were seen, and the mean age at diagnosis was 12.3 years. The commonest presenting features were short stature alone seen in 37 (65.45%) and short stature with delayed puberty in 18 (32.72%). The earliest age at presentation was 4.5 years who presented with short stature. The mean height was 124.17 cm and mean BMI 17.54 kg/m2. The most common karyotype was 45, XO found in 34 (61.6%) of the cases. 15 (27.27%) the cases were started on growth hormone therapy. 26 cases (47.27%) required pubertal induction. Conclusion: A vast number of cases with TS in India remain undiagnosed until puberty or present very late. A high degree of clinical suspicion can help us diagnose these children earlier. If TS is diagnosed earlier, growth can be achieved up to their maximum potential. Early identification and management will help us provide multidisciplinary care and hence prevent complications.